Development of Mobile Application for Shoe Washing Services based on Android with Kotlin - Maulana, Shendy Fachrian; Pramudwiatmoko, Arif (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Businesses in the form of services continue to grow, although many service providers still face challenges in improving operational efficiency and service quality because they still use manual systems to manage orders and customer data, which are often not integrated. This research aims to design and build a mobile-based shoe washing service application with a focus on Pojok Shoescare. This application aims to make it easier for customers to order shoe washing services online and provide convenience for admins in managing customer and order data. A web-based admin dashboard was developed to enable more structured data management. The development method used in application development is Rapid Application Development (RAD) because it is flexible and able to accelerate the development cycle. Results from BlackBox testing show that the application runs optimally and meets user needs related to ease of use and service efficiency. This application is expected to improve the quality of service at Pojok Shoescare and provide a better experience for customers in ordering shoe washing services and supporting business growth in the future. Keywords: Android, Mobile application, Online ordering, Rapid application development, Shoe washing services